Teacher Identity: Influence of Emerging Trends (International Conference on Computers in Education, 2017)
Using a qualitative research method, the study aims to analyze the teacher identity and how such an identity is being influenced by current technology trends in educational practice. Sample of the study was composed of five teachers, with teaching experiences of 8 to10 years. The interview technique was used as the data collection instrument. The recorded interviews were transcribed and analysis was carried out on this dataset. The result showed that teachers form their professional identity based on the expectations and conditions after they take up appointment as teachers, identities continue to change and develop along practice, societal recognitions, as well as life experiences. Further, findings of the study are discussed as reflection of teachers’ work environment and development.